2022
DOI: 10.1177/02673231221118192
|View full text |Cite
|
Sign up to set email alerts
|

Tools and measures for diversity and inclusion in media industries: International best practice and informing policy change in the Irish film and television sector

Abstract: This article focuses on equality, diversity and inclusion in the Irish media industry and how it can be improved. The need to develop these policies, tools and measures has become pertinent, considering that the Irish media workforce currently lacks diversity. The aims of this article are twofold: (i) examine the tools and measures from the international media industry that have been developed to improve equality, diversity and inclusion and (ii) interrogate how these tools and measures could work within the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…They were asked to document key moments and interventions that led to change. Further interviews were undertaken as part of a research project for the BAI (Kerrigan, Liddy & O' Brien, 2021) to audit attitudes and approaches to equality and diversity in 2020-2021. Data were gathered through semi-structured, indepth interviews done by the authors as described in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…They were asked to document key moments and interventions that led to change. Further interviews were undertaken as part of a research project for the BAI (Kerrigan, Liddy & O' Brien, 2021) to audit attitudes and approaches to equality and diversity in 2020-2021. Data were gathered through semi-structured, indepth interviews done by the authors as described in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…Kerrigan, P et al examined development initiatives in the Irish media industry in relation to equality, diversity and inclusion. Four core areas were identified in the results: data collection and monitoring, development of diversity standards, target setting and incentives, and diversity recruitment in the industry [13]. Chen, H et al examined the mechanisms by which Chinese kung fu films and TV movies influence the image perception of tourist destinations and found that audience engagement can, directly and indirectly, influence viewers' perceptions of wuxia culture and enhance the image of tourist destinations through cultural encounters perception [14].…”
Section: Introductionmentioning
confidence: 99%